SPE Annual Technical Conference and Exhibition 2006
DOI: 10.2118/101950-ms
|View full text |Cite
|
Sign up to set email alerts
|

Study on Flow Behaviors of Viscoelastic Polymer Solution in Micropore With Dead End

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe Upper-Convected Maxwell (UCM) model has been normally used to describe the rheological properties of polymer solutions. However, this model considers only viscosity and elasticity of a fluid without including the non-Newtonian power law behavior, a very important property to polymer solutions in reservoirs. Therefore, we present a Modified Upper-Convected Maxwell (MUCM) in this paper to take into account this property.The steady flow mathematical model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 9 publications
0
23
0
1
Order By: Relevance
“…This effect has been further investigated through numerical simulation of polymer flooding over dead ends (Yin et al 2006(Yin et al , 2012Xia et al 2008a, b;Zhang and Yue 2008). The pulling effect also works for residual oil trapped in a configuration that have both ends open to flow.…”
Section: Mechanisms Enhancing Microscopic Displacement Efficiencymentioning
confidence: 99%
“…This effect has been further investigated through numerical simulation of polymer flooding over dead ends (Yin et al 2006(Yin et al , 2012Xia et al 2008a, b;Zhang and Yue 2008). The pulling effect also works for residual oil trapped in a configuration that have both ends open to flow.…”
Section: Mechanisms Enhancing Microscopic Displacement Efficiencymentioning
confidence: 99%
“…To study the stability of oil threads, they derived relevant fluid flow equations but no solutions to the problem were given. In order to model the scouring of oil from a dead-end pore by a viscoelastic polymer solution, Yin et al (2006) solved the relevant flow equations numerically, and qualitatively showed the feasibility of the scouring mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…A mobilização de óleos retidos em microcavidades têm sido estudada desde a perspectiva monofásica (Yin, 2006;Kamyabi, Ramazani & Kamyabi, 2013;Pena, Romero & Ribeiro, 2014;Kamyabi, Ramazani & Kamyabi, 2015) e mais recentemente bifásica (Coelho, Pena & Romero, 2016). A maioria das geometrias utilizadas são microcavidades quadradas com quinas agudas.…”
Section: Introductionunclassified